2014
DOI: 10.1111/ejss.12172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of silicate minerals as sources of potassium for plant nutrition in sandy soil

Abstract: Summary Given the cost of conventional fertilizers and increasing demand as a result of increasing population growth, new sources of potassium (K) for plant nutrition need to be considered. Readily soluble nutrients are rapidly lost from well‐drained soils, and so it is appropriate to consider silicate minerals that release K slowly during weathering. In this paper, we compare the availability to plants grown in sandy soils of K from microcline (feldspar), biotite (mica) and nepheline syenite (nepheline + micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 27 publications
2
33
2
4
Order By: Relevance
“…Many rocks containing K silicate minerals can be used as alternative raw materials in K fertilizer production, mainly in those countries with limited soluble K minerals such as sylvite, arcanite, carnalite, and langbeinite. In addition, studies have shown that other rock types and minerals, such as nepheline syenite ( Bakken et al, 2000; Nascimento , 2004), biotite ( Mohammed et al, 2014), zinnwaldite mica ( Madaras et al, 2013), and glauconitic rock ( Mazumder et al, 1993; Santos et al, 2015), are viable sources of K.…”
Section: Discussionmentioning
confidence: 99%
“…Many rocks containing K silicate minerals can be used as alternative raw materials in K fertilizer production, mainly in those countries with limited soluble K minerals such as sylvite, arcanite, carnalite, and langbeinite. In addition, studies have shown that other rock types and minerals, such as nepheline syenite ( Bakken et al, 2000; Nascimento , 2004), biotite ( Mohammed et al, 2014), zinnwaldite mica ( Madaras et al, 2013), and glauconitic rock ( Mazumder et al, 1993; Santos et al, 2015), are viable sources of K.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the recent high price of potash, and the need to supply K to land that is distant from readily available sources of conventional K, have led to increased interest in alternatives. The micas appear to be able to give crop yields similar to conventional KCl: Mohammed et al (2014) show that equivalent applications of biotite and KCl give similar yields of leeks. Madaras et al (2012) demonstrate that zinnwaldite (a mica associated with tin mineralization) is effective as a source of K for barley, as is acid-treated phlogopite for rice (Weerasuriya et al, 1993).…”
Section: Tablementioning
confidence: 86%
“…Madaras et al (2012) demonstrate that zinnwaldite (a mica associated with tin mineralization) is effective as a source of K for barley, as is acid-treated phlogopite for rice (Weerasuriya et al, 1993). These observations arise from the demonstrable ability of the micas to weather in soils, where they influence the availability of K through cation exchange (Mohammed et al, 2014). In contrast, framework silicates such as K-feldspar and nepheline release K through weathering of a three-dimensional covalent aluminosilicate network.…”
Section: Tablementioning
confidence: 99%
“…However, careful experimental design is required to demonstrate that the K required for plant growth has indeed come from the silicate mineral that has been applied. For example, Mohammed et al (2014) considered the mineralogical composition specifically of the soil used in experimental trials, showing that a statistically significant plant response to application of feldspar is observed for artificial and natural sandy soils that lacked feldspar. In contrast, studies that used soil that already included the minerals applied as treatments (i.e., the added mineral is weathering at the same rate as those already in the soil) showed no growth response (e.g., Ramezanian et al 2013).…”
Section: Novel Sources Of K As a Crop Nutrientmentioning
confidence: 99%